2012
DOI: 10.1016/j.dsr.2012.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic carbon and pH levels in the Rockall Trough 1991–2010

Abstract: The accumulation of anthropogenic CO 2 in the oceans is altering seawater carbonate chemistry. Monitoring carbonate parameters is therefore necessary to understand potential impacts on ocean ecosystems. Total alkalinity (A T ) and dissolved inorganic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 71 publications
(57 reference statements)
1
24
0
Order By: Relevance
“…Within the 68 % confidence intervals, the NA-SPSS pH trend is consistent with both of these local trends. In the North Atlantic subtropical seasonally stratified (NA-STSS) biome, there are no time series data to compare with, but its trend of −0.0018 ± 0.0003 yr −1 is consistent with a trend of ∼ −0.0020 yr −1 observed in the Rockall Trough by McGrath et al (2012). In the North (NA-STPS) and South (SA-STPS) Atlantic subtropical permanently stratified biomes, the pH trend is the same, but the RMSE values indicate larger interannual variability in the southern biome (Table 1).…”
Section: Long-term Trends In Phmentioning
confidence: 67%
“…Within the 68 % confidence intervals, the NA-SPSS pH trend is consistent with both of these local trends. In the North Atlantic subtropical seasonally stratified (NA-STSS) biome, there are no time series data to compare with, but its trend of −0.0018 ± 0.0003 yr −1 is consistent with a trend of ∼ −0.0020 yr −1 observed in the Rockall Trough by McGrath et al (2012). In the North (NA-STPS) and South (SA-STPS) Atlantic subtropical permanently stratified biomes, the pH trend is the same, but the RMSE values indicate larger interannual variability in the southern biome (Table 1).…”
Section: Long-term Trends In Phmentioning
confidence: 67%
“…The storage rates of DIC and DICabio in the southern parts of regions A and B are significantly higher than for the northern parts, and conform better to published estimates of C ant in the region. For instance, a recent study by McGrath et al (2012) found storage rates of C ant in the Rockall Trough of 1.2 mol m −2 a −1 for the layer between 200 and 2000 m. The oxygen and AOU storage rates are close to neutral in the southern parts of regions A and B, i.e. similar to other areas further south in the Atlantic.…”
Section: Discussionmentioning
confidence: 88%
“…A very small portion of this may be related to the lower salinity observed, however such a large difference is unlikely to be true. This negative offset in the 2009 TA data had previously been observed through the water column (therefore not due to CaCO 3 formation) and so was not included in McGrath et al (2012a). Preliminary results suggest that this parameter will be adjusted in the second version of the GLODAP database, which is currently being developed.…”
Section: Secondary Quality Controlmentioning
confidence: 99%
“…It is unclear why the TA CRMs for Batch 102 used for CE10002 had a slightly larger offset than other batches. Vertical profiles of final TA concentrations from this survey were cross-checked with TA profiles from CE12001 and two WOCE (World Ocean Circulation Experiment) surveys in the same region (McGrath et al, 2012a). All suggest that there is no problem/offset in the TA results generated from this batch.…”
Section: Quality Controlmentioning
confidence: 99%
See 1 more Smart Citation